Hand tracking, palm and finger recognition towards touch-less device interaction - Jelliti, Ibrahim; Grudzień, Krzysztof; Romanowski, Andrzej; Woźniak, Paweł (Wydawnictwo Politechniki Łódzkiej, 2016)
Hand recognition is a computer technology used to spot a hand as well as to determine the location of hand and its position in arbitrary digital images. The advances in mobile industry have made the complex calculations possible and feasible in smartphones. Taking advantage of these developments, we aimed to develop a gesture recognition application based on a computer vision and image processing algorithms. The application is be able to recognize the fingers of the hand and tracking their moves to perform some interaction with the mobile environment. Presented system is a technical platform for further study of mobile-mixed reality in the field of human-computer interaction.
Keywords: mobile interaction; hand recognition; hand gesture; interpretation; image processing; interakcja mobilna; rozpoznawanie dłoni; gest ręki; interpretacja; przetwarzanie obrazu